ANALISIS KUALITAS LAYANAN INOVASI LISTRIK PRABAYAR DALAM MENINGKATKAN KEPUASAN PELANGGAN PADA PT. PLN (PERSERO) CABANG KENDARI - Handayani, Putri (Business UHO: Jurnal Administrasi Bisnis, 2016)
Technics withdrawal by accidental sampling is that sampling technique based on chance, that spas are incidentally, that anyone who by chance met with investigators.thus, ini this study the number of samples used as many 50 people. Data analysis method used is quantitative analisis. The results showed the quality of service innovation and significant positive effect on customer satisfaction. Keywords : Quality of Service, Innovation and customer satisfaction